A Rare Case Report of Extensive Polyostotic Gorham's Disappearing Bone Disease Involving the Upper Extremity. (10th December 2011) - Ahlmann, Elke R.; Ma, Yanling; Tunru-Dinh, Vonny
Abstract : Gorham's disease is a rare disorder involving the proliferation of endothelial channels resulting in resorption and disappearance of bone. An unusual case of polyostotic Gorham's disease affecting the scapula, humerus, radius, and ulna in a 39-year-old woman is described. The patient had extensive disease spreading across both the glenohumeral and humeroulnar joints. This is the first report of Gorham's disease spreading across multiple joints in the upper extremity.